2022
DOI: 10.3390/ma15248911
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Research on the Use of Geopolymer Recycled Aggregate Concrete for Structural Members

Abstract: Geopolymer cement (GPC) is a sustainable alternative to ordinary Portland cement (OPC) that considerably cuts the emission of carbon dioxide linked to the building of concrete structures. Over the last few decades, while a large number of papers have been written concerning the use of GPC with natural aggregates and OPC with recycled aggregates, few papers have been devoted to investigating the use of Geopolymer Recycled Aggregate Concrete (GRAC) in structural members. Most of them show more interest in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Furthermore, in [30], it was also shown that-due to the presence of both natural fibers-the failure mode of the composite changes from a brittle to more ductile one and that the post-peak behavior is strongly influenced. On the other hand, the role played by geopolymers in the construction industry is confirmed by many papers in which the use of geopolymers as the basis of concrete (with or without recycled aggregates) to be adopted in structural members is investigated [31].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore, in [30], it was also shown that-due to the presence of both natural fibers-the failure mode of the composite changes from a brittle to more ductile one and that the post-peak behavior is strongly influenced. On the other hand, the role played by geopolymers in the construction industry is confirmed by many papers in which the use of geopolymers as the basis of concrete (with or without recycled aggregates) to be adopted in structural members is investigated [31].…”
Section: Introductionmentioning
confidence: 94%
“…In developing the research program, the elimination of Portland cement, previously the main component of concrete, was a priority. Studies have shown that producing one ton of cement releases 0.9 tons of CO 2 , accounting for 5% to 7% of global CO 2 emissions [1][2][3]. Many studies have shown that geopolymer concrete is an alternative to cement-based concrete, and its synthesis is a process that consumes half the energy required for Portland cement production and releases 80% less carbon dioxide [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…In developing the research program, the elimination of Portland cement, previously the main component of concrete, was a priority. Studies have shown that producing one ton of cement releases 0.9 tons of CO2, accounting for 5% to 7% of global CO2 emissions [4,14,19]. Many studies have shown that geopolymer concrete is an alternative to cement-based concrete, and its synthesis is a process that consumes half the energy required for Portland cement production and releases 80% less carbon dioxide [3,11,13,23].…”
Section: Introductionmentioning
confidence: 99%